In vitro thrombolytic activity of Moringa oleifera - BHAVIKA KUNWAR; VARTIKA JAIN; S. K. VERMA (Smujo International, 2022)
Abstract. Kunwar B, Jain V, Verma SK. 2022. In vitro thrombolytic activity of Moringa oleifera. Nusantara Bioscience 14: 63-69. Moringa oleifera Lam. (Family Moringaceae) is a medium-sized perennial tree, commonly known as drumstick tree, horse radish tree, miracle tree, sahjan, shobhanjana, munga arak, etc., in different languages. Leaves, flowers, and pods of the plant are edible. Various parts of the plant are utilized to treat several diseases by ethnic communities, including heart ailments. Leaves and flowers of M. oleifera were assessed for preliminary qualitative phytochemical analysis and in vitro thrombolytic potential. Preliminary phytochemical screening has shown the presence of flavonoids, terpenoids, cardiac glycosides, saponins, tannins, amino acids, and carbohydrates in the leaves and flowers of M. oleifera. Two types of methanolic extracts of both leaves (MEL-I and MEL-II) and flowers (MEF-I and MEF-II) were used to assess percent clot lysis. A significant in vitro clot lysis activity of MEL-I (36.64±1.55%), MEL-II (41.40±2.02%), and MEF-I (19.07±2.36%), and MEF-II (20.52±1.51%) was demonstrated in a concentration of one mg/mL as compared to negative control distilled water and positive control streptokinase for the first time. The edible plant's observed thrombolytic potential may be employed to prevent athero-thrombotic cardiovascular diseases. Further investigations are required to isolate the bioactive molecule responsible for the thrombolytic action.